2016
DOI: 10.4236/ajor.2016.62014
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Spare Parts Demand Using Statistical Analysis

Abstract: Spare parts are very essential in most industrial companies. They are characterized by their large number and their high impact on the companies' operations whenever needed. Therefore companies tend to analyze their spare parts demand and try to estimate their future consumption. Nevertheless, they face difficulties in figuring out an optimal forecasting method that deals with the lumpy and intermittent demand of spare parts. In this paper, we performed a comparison between five forecasting methods based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…The results obtained by Hemeimat et al [31] show that moving averages can provide very competitive forecasts, compared with other techniques, even in the case of exponential smoothing, which has been found not …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The results obtained by Hemeimat et al [31] show that moving averages can provide very competitive forecasts, compared with other techniques, even in the case of exponential smoothing, which has been found not …”
Section: Resultsmentioning
confidence: 97%
“…It is also important to identify the nature of the item under study. This can be achieved when classifying them under different criteria, according to our needs and several studies on this matter have been performed, with classifications based on the periodicity of the demand [28], the manufacturing volume [29], or even more complex classifications [30] that should be of help for selecting proper methods and tools for modeling spare-parts behaviour [31]. Based on the literature review up to this point, it was possible to decide that the best tool for modelling the automobile spare-parts demand, given its behaviour and little availability of information, is by means of a time series perspective, so that it has been decided to develop the ARIMA and ANNs models using only the information available in order to obtain forecasts.…”
Section: Spare-parts Demand Forecastingmentioning
confidence: 99%
“…The current method is moving average which is used to forecast for every pattern of demand whether it is intermittent, lumpy, erratic, or smooth, but different spare parts associate diverse demand patterns and forecasting methods (Hemeimat et al, 2016). The aim of current study is to investigate the prevailing forecasting approaches for intermittence demand and select the demand estimations to upsurge forecasting performance of the selected auto service station.…”
Section: Methodsmentioning
confidence: 99%
“…(TSB). The results indicated that Root Mean Square Error (RMSE) showed closer performances for all the five approaches [12]. Another study on spare parts of aircraft revealed that it is meaningful to measure performance based on the quality of repairs rather than the level of spare parts.…”
Section: Literature Backgroundmentioning
confidence: 97%